PERBEDAAN PENGARUH BESARAN PERUSAHAAN DAN LEVERAGE TERHADAP MANAJEMEN LABA PADA PERUSAHAAN YANG MEMILIKI KOMITE AUDIT DAN DIAUDIT OLEH AUDITOR BERKUALITAS - EKA DAMAYANTHI, I G. A. (Jurnal Ilmiah Akuntansi dan Bisnis, 2008)
This research examines the effect of existence of audit committee and qualified auditor on the relationship between company’s size and leverage, and earnings management. This study is motivated by inconsistence results of previous studies on this topic. Supported by agency theory explaining problem between the agent and the principal, researcher is motivated to contribute on the importance of monitoring management performance by audit committee and qualified independent auditor. Sample consists of 364 manufacturing companies listed on the Jakarta Stock Exchange during 1999-2003. Earnings management is measured by discretionary accrual calculated using modified Jones Model. The effect of audit committee on the relationship between size and leverage is tested using coefficient difference test. The result shows that large companies tend to have small discretionary accrual, thus it would have better quality earnings. The existence of audit committee could reduce the effect of leverage on earnings management. Qualified auditor could diminish the effect of size and leverage on earnings management.
Keywords: company’ size, leverage, earnings management, audit committee, qualified auditor.